An In-Situ MRI Method for Quantifying Temperature Changes during Crystal Hydrate Growths in Porous Medium - Zhang, Lunxiang; Sun, Mingrui; Wang, Tian; Yang, Lei; Zhang, Xiaotong; Zhao, Jiafei; Song, Yongchen (Journal of thermal science, 2022)
Given the complexity of the thermo-hydro-chemically coupled phase transition process of hydrates, real-time in-situ observations are required. Thermometry maps are particularly essential in analyzing the heat transfer process during the growth and dissociation of crystal hydrates. In this study, we present the temporally and spatially resolved thermometry of the formation of tetrahydrofuran hydrates based on the temperature dependence of the chemical shift of the water proton. Images of temperature changes were synchronously obtained using a 9.4 T 1 H magnetic resonance imaging (MRI) system to predict the saturation level of the aqueous solution, phases of the solid hydrates, and the positive temperature anomaly of the exothermic reaction. It was observed that variations in the MRI signal decreased while the temperature rise differed significantly in space and time. The results predicted in this study could have significant implications in optimizing the phase transition process of gas hydrates.